2015
DOI: 10.1002/er.3341
|View full text |Cite
|
Sign up to set email alerts
|

Critical heat flux enhancement in pool-boiling heat transfer using oxidized multi-wall carbon nanotubes

Abstract: Summary In this study, the critical heat flux (CHF) and heat‐transfer coefficient under the pool‐boiling state were tested using multi‐wall carbon nanotubes (MWCNT) CM‐95, CM‐100, and oxidized MWCNT CM‐100. The results showed that the highest CHF increase for both MWCNT CM‐95 and CM‐100 was at the volume fraction of 0.001%, and that the CHF increase ratio for MWCNT CM‐100 nanofluid with long particles was higher than that for MWCNT CM‐95 nanofluid with short particles. In addition, at the volume fraction of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…They reported that so long as nanoparticle concentration increases, the boiling heat transfer coefficient increases. As a consequence of their experimental study, Park and Kim (2015) obtained a 21.04% increment in the boiling heat transfer coefficient when they used CM-100 nanoparticles-containing nanofluid. For after-saturation pool boiling conditions, nanofluid usage slightly improved the heat transfer coefficients compared to results attained under saturation conditions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…They reported that so long as nanoparticle concentration increases, the boiling heat transfer coefficient increases. As a consequence of their experimental study, Park and Kim (2015) obtained a 21.04% increment in the boiling heat transfer coefficient when they used CM-100 nanoparticles-containing nanofluid. For after-saturation pool boiling conditions, nanofluid usage slightly improved the heat transfer coefficients compared to results attained under saturation conditions.…”
Section: Resultsmentioning
confidence: 95%
“…Accordingly, nanofluids have been successfully used for improving the thermal performance of boiling–condensation processes. Park and Kim (2015) conducted an experimental study for specifying the critical heat flux (CHF) and heat transfer coefficient for multi-wall carbon nanotubes (CM-95 and CM-100) and oxidized-type multi-wall carbon nanotube under pool boiling conditions. They attained the highest CHF increment in their test performed by using the nanofluid that has 0.001% nanoparticle concentration.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, Liu et al also studied boiling with pure water on a CNTs-coated surface and observed that the CNTs nanofluids provided better increase for both CHF and nucleate BHTCs. Park and Kim 23 stated that at a concentration of 0.001 vol % multi-walled CNTs the nanofluids optimally increased the CHF and HTC of nucleate boiling. Park and Jung 24 concluded up to 30% rise in HTC of the nucleate boiling using hydrochlorofluorocarbon better known as R22-and water-based 1.0 vol % CNT nanofluids.…”
Section: Literature Reviewmentioning
confidence: 99%
“…nanowires [18][19][20], nanotubes [21][22][23] and nanopores [24,25] have been widely used to strengthen the pool boiling heat transfer. Copper foam as a promising porous media has been employed extensively in heat dissipation due to its high porosity and high specific surface area.…”
Section: Introductionmentioning
confidence: 99%